Tingkat Stres Dosen Perempuan UII Ditinjau Dari Dukungan Suami - Retno Kumolohadi (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2001)
This research aimed to examine the relationship between level of stress and social support from husba.nd The hypothesis was tested there was a negative coreteuon between level of stress and social support from husband.The subjects of this research were 30 women lecturer from Islamic Unntersity of Indonesia. The data collection was done using the quetionaire method for the scale of stress and social support from husband.The refationship between level of stress and social support from hus band used by product moment analysis. The result ofcorreteuon analysis was r